2020
DOI: 10.1111/gcb.15189
|View full text |Cite
|
Sign up to set email alerts
|

Global changes may be promoting a rise in select cyanobacteria in nutrient‐poor northern lakes

Abstract: Northern ecosystems are anticipated to undergo the greatest rates of climate change (Hansen et al., 2006; IPCC, 2007). Climate changes in northern (>45° North) ecosystems include increasing temperatures (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 117 publications
0
40
0
3
Order By: Relevance
“…The relatively low total phytoplankton biovolume in ERA5 is explained by the small sized cells, making the high biovolume of cyanobacteria even more striking. Several small celled cyanobacterial groups, including the species of Chroococcales such as Chroococcus found in ERA5, are considered indicators of increasing P and high N concentrations (Andersson et al 2015;Freeman et al 2020) in addition to the green alga, Pediastrum, which was only found in ERA5, with a prevalence of 11.2% of phytoplankton biovolume (Table S1). Pediastrum has been associated with increased primary production driven by recent climate change in subarctic and high Arctic lakes (Rühland et al 2013;Woelders et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low total phytoplankton biovolume in ERA5 is explained by the small sized cells, making the high biovolume of cyanobacteria even more striking. Several small celled cyanobacterial groups, including the species of Chroococcales such as Chroococcus found in ERA5, are considered indicators of increasing P and high N concentrations (Andersson et al 2015;Freeman et al 2020) in addition to the green alga, Pediastrum, which was only found in ERA5, with a prevalence of 11.2% of phytoplankton biovolume (Table S1). Pediastrum has been associated with increased primary production driven by recent climate change in subarctic and high Arctic lakes (Rühland et al 2013;Woelders et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The warming of surface waters directly benefits cyanobacteria because their growth rates can peak between 25 and 35°C (Huisman et al, 2018; Paerl & Huisman, 2009; Richardson et al, 2019), and evidence from marine systems indicates that cyanobacteria may adapt to warming temperatures at faster rates than do other groups of phytoplankton (Barton et al, 2020). Growth rates of other phytoplankton decline once they exceed optimal temperatures of 15–25°C (Huisman et al, 2018; Paerl & Huisman, 2008, 2009), though changes in growth rate responses can be quite variable among species and strains within all groups of phytoplankton (Huisman et al, 2018; Lürling et al, 2013; Rigosi et al, 2014) and other factors can be important and affect taxa differently (Freeman et al, 2020). In non‐stratifying reservoirs, surface temperatures on average are 25.5°C in June, after increasing by 2.4°C since 1989.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments indicate that cyanobacteria have optimal growth rates at warmer temperatures than those of other groups of phytoplankton, such as diatoms and cryptomonads (Carey et al, 2012; Huisman et al, 2018; Paerl & Huisman, 2009), and their growth rates respond to warming waters more quickly than those of green algae (Visser et al, 2016), despite evidence of having similar optimal temperatures for growth (Lürling et al, 2013; Paerl et al, 2016). As a result, differences in the temperature dependence of phytoplankton growth rates can contribute to greater cyanobacteria abundances in warmer waters, even when nutrient concentrations are low (Freeman et al, 2020; Kosten et al, 2012; O'Neil et al, 2012). Warming trends, in combination with changes in water clarity, also increase the strength and duration of thermal stratification in lentic ecosystems (Kraemer et al, 2015; Richardson et al, 2017; Rose et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As the overall function of aquatic ecosystems alteration in Summer, such as biochemical transformations of nutrients (Wu et al 2017;Ding et al 2018;Jenny et al 2020), there might create an environment which is particularly beneficial for phytoplankton surviving (e.g. cyanobacteria) and result in HABs (Paerl et al 2016;Freeman et al 2020). From the results, although stopping operation and high temperature could affect the removal rates of the bioreactor, there had little influence on the purification effect when the bioreactor was running, showing the good effect of the bioreactor.…”
Section: Season-changing and Stopping Operation Affect The Removal Rate Of The Bioreactormentioning
confidence: 94%
“…In recent decades, aquatic ecosystem has suffered much more serious problems of water eutrophication due to anthropogenic pollution and climate change (Le et al 2010;Smith 2003;Kosten et al 2012;Andersen et al 2020a;Freeman et al 2020).…”
Section: Introductionmentioning
confidence: 99%